EFEKTIVITAS PENGGUNAAN ALAT PERCOBAAN PESAWAT SEDERHANA BERBASIS PERALATAN BUDAYA TRADISIONAL SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPA SMP - Annur Miftahul Jannah; Hendar Sudrajat; Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to know the effectiveness of th of a simple machine experiment equipment based traditional culture as a medium of learning to improve students’ motivation in science learning of SMP. This research was done with the One-Group Pretest-Posttest Desaign. The subjects were students of class VIII SMP Muhammadiyah Kuok applying simple machine experiment equipment based traditional culture as a medium of learning. The instruments used in data collection nomina was a questionnaire motivation ARCS consisting of indicator Attention, Relevance, Confidence, and Satisfaction. Data were analyzed students’ motivation to learn physics through descriptive analysis. The results of data analysis, for attention indicator values obtained for the gain of 0.46 with intermediate categories. for relavance indicator values obtained for the gain of 0.37 with intermediate categories. for convidence indicator values obtained for the gain of 0.51 with intermediate categories. for satisfaction indicator values obtained for the gain of 0.40 with intermediate categories. And for to all syudents obtained for the gain of 0.43 with intermediate categories. From the result of data analysis can be concluded thet learning use of a simple machine experiment equipment based traditional culture as a medium of learning to increase students’ motivation is said the effectiveness of the intermediate category.Keywords: Effectiveness, Students’ Motivation, medium of learning, Traditional culture